Risk of stroke/systemic embolism, major bleeding and associated costs in non-valvular atrial fibrillation patients who initiated apixaban, dabigatran or rivaroxaban compared with warfarin in the United States Medicare population. (2nd September 2017) - Amin, Alpesh; Keshishian, Allison; Trocio, Jeffrey; Dina, Oluwaseyi; Le, Hannah; Rosenblatt, Lisa; Liu, Xianchen; Mardekian, Jack; Zhang, Qisu; Baser, Onur; Vo, Lien
Abstract: Objective: To compare the risk and cost of stroke/systemic embolism (SE) and major bleeding between each direct oral anticoagulant (DOAC) and warfarin among non-valvular atrial fibrillation (NVAF) patients. Methods: Patients (≥65 years) initiating warfarin or DOACs (apixaban, rivaroxaban, and dabigatran) were selected from the Medicare database from 1 January 2013 to 31 December 2014. Patients initiating each DOAC were matched 1:1 to warfarin patients using propensity score matching to balance demographics and clinical characteristics. Cox proportional hazards models were used to estimate the risks of stroke/SE and major bleeding of each DOAC vs. warfarin. Two-part models were used to compare the stroke/SE- and major-bleeding-related medical costs between matched cohorts. Results: Of the 186, 132 eligible patients, 20, 803 apixaban–warfarin pairs, 52, 476 rivaroxaban–warfarin pairs, and 16, 731 dabigatran–warfarin pairs were matched. Apixaban (hazard ratio [HR] = 0.40; 95% confidence interval [CI] 0.31, 0.53) and rivaroxaban (HR = 0.72; 95% CI 0.63, 0.83) were significantly associated with lower risk of stroke/SE compared to warfarin. Apixaban (HR = 0.51; 95% CI 0.44, 0.58) and dabigatran (HR = 0.79; 95% CI 0.69, 0.91) were significantly associated with lower risk of major bleeding; rivaroxaban (HR = 1.17; 95% CI 1.10, 1.26) was significantly associated with higher risk of major bleeding compared to warfarin. Compared to warfarin, apixaban (63 vs. 131) and rivaroxaban (93 vs. 139) had significantly lower stroke/SE-related medical costs; apixaban (292 vs. 529) and dabigatran (369 vs. 450) had significantly lower major bleeding-related medical costs. Conclusions: Among the DOACs in the study, only apixaban is associated with a significantly lower risk of stroke/SE and major bleeding and lower related medical costs compared to warfarin.